PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERPEN PADA PESERTA DIDIK KELAS XI MIA 10 SMA NEGERI 7 DENPASAR TAHUN PEMBELAJARAN 2018/2019 - Widiawati, Cokorda Istri Mirah Kusuma (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
The purpose of this research is to find out whether the application of inquiry learning models can improve the ability to analyze short story intrinsic elements and can improve students' responses. This study uses a class action research design (PTK), there are four important components in the PTK cycle, namely: (1) the planning stage, (2) the stage of action, (3) the stage of observation and, (4) the stage of reflection. This research was carried out in the odd semester of August to September 2018. The research subjects were students of class XI MIPA 10 in SMA Negeri 7 Denpasar in the academic year 2018/2019 with a total of 36 students. The object of this class action research is the ability to analyze short story intrinsic elements. The results of this study indicate increasing the ability to analyze short story texts (1) The acquisition of the average grade value at the initial reflection of 65.64 increased in the first cycle to 73.42 and in the second cycle it increased to 82.03. (2) Increasing the value from cycle I to cycle II occurs in 28 students or 77.78%. The percentage of success of students in learning to analyze the intrinsic elements of short stories reaches classical completeness 94.44% of the number of students get 70 and above. The application of the inquiry learning model in learning analyzes the intrinsic elements of the short story to get a positive response from students (1) The acquisition of the average class response value in the first cycle is 69.12 and in the second cycle it increases to 84.31. (2) Percentage of responses of students in learning to analyze the short story intrinsic elements with the application of inquiry learning models achieving classical completeness, namely 94.44%.